Efficacy of T-705 (Favipiravir) in the Treatment of Infections with Lethal Severe Fever with Thrombocytopenia Syndrome Virus - Tani, Hideki; Fukuma, Aiko; Fukushi, Shuetsu; Taniguchi, Satoshi; Yoshikawa, Tomoki; Iwata-Yoshikawa, Naoko; Sato, Yuko; Suzuki, Tadaki; Nagata, Noriyo; Hasegawa, Hideki; Kawai, Yasuhiro; Uda, Akihiko; et al. (mSphere, 2016)
Severe fever with thrombocytopenia syndrome (SFTS), caused by SFTS virus (SFTSV), is a recently identified emerging viral infectious disease. Despite the medical importance of this disease, there are currently neither vaccines nor effective therapeutics for SFTS. T-705, which is a pyrazine derivative, has shown broad antiviral activity against various RNA viruses. The present study demonstrated, for the first time to our knowledge, the efficacy of T-705 in treating SFTSV infection in a mouse lethal model. T-705 showed a high efficacy in the treatment of SFTSV infection in the mouse model, even when treatments were initiated after onset of the disease. Severe fever with thrombocytopenia syndrome virus (SFTSV) is the causative agent of SFTS, an emerging hemorrhagic fever. This disease has a high case fatality rate and is endemic to China, South Korea, and Japan. Because there are currently no effective therapeutics for SFTS, potent and safe antivirals are needed for the treatment of SFTS. The inhibitory effect of T-705 (favipiravir) on the replication of SFTSV in Vero cells was evaluated. Mice lacking the type I interferon receptor (IFNAR −/− ) were used as an in vivo lethal model for SFTSV infection. T-705, which has been licensed as an anti-influenza drug in Japan, inhibits SFTSV replication both in vitro and in vivo . T-705 inhibited replication of SFTSV in Vero cells by 5 log units, with a 50% inhibitory concentration (IC 50 ) and IC 90 of 6.0 µM and 22 µM, respectively. Intraperitoneal or oral administration of T-705 for 5 days to IFNAR −/− mice infected with lethal SFTSV significantly improved survival rates (100% survival) without causing body weight loss and reduced the viral load in the serum. Ribavirin also inhibited SFTSV replication. However, it was less effective than T-705 both in vitro and in vivo . A time-of-drug-addition study revealed that therapeutic T-705 treatment of SFTSV infection in IFNAR −/− mice was effective. These results suggest that T-705 is a promising candidate for the treatment of SFTS. IMPORTANCE Severe fever with thrombocytopenia syndrome (SFTS), caused by SFTS virus (SFTSV), is a recently identified emerging viral infectious disease. Despite the medical importance of this disease, there are currently neither vaccines nor effective therapeutics for SFTS. T-705, which is a pyrazine derivative, has shown broad antiviral activity against various RNA viruses. The present study demonstrated, for the first time to our knowledge, the efficacy of T-705 in treating SFTSV infection in a mouse lethal model. T-705 showed a high efficacy in the treatment of SFTSV infection in the mouse model, even when treatments were initiated after onset of the disease.